Product-service systems and circular supply chain practices in UK SMEs: The moderating effect of internal environmental orientation - Kühl, Carl; Bourlakis, Michael; Aktas, Emel; Skipworth, Heather (Elsevier, 2022)
Many studies uphold product-service systems (PSSs) as key factors for the implementation of circular supply chain (CSC) practices. This paper explores this assumption by testing the links between product-, use- and result-oriented PSSs and slowing, closing, and narrowing CSC practices. It develops and validates survey items that can be used to benchmark CSC practice implementation. In addition, it tests a model that recognises the positive moderating role of internal environmental orientation. A survey is conducted with 114 manufacturing small and medium-sized enterprises (SMEs) in the United Kingdom (UK). Partial least squares structural equation modelling is conducted to evaluate two models. The results show that product-oriented PSSs positively affect the slowing, use-oriented positively affects the closing, and result-oriented positively affects the slowing and the narrowing of resource loops. Internal environmental orientation does not moderate the PSS – CSC relationship, suggesting that less internally environmentally oriented firms are not at a disadvantage.
Keywords: Circular economy; product-service system (PSS); supply chain; partial least squares structural equation modelling (PLS-SEM)